LEARNING ENGLISH WORD CLASS BY USING CONCORDANCE SOFTWARE - Yogi Setia Samsi (ELT in Focus, 2018)
Concordance is one of the software based corpus linguistics which aims to analyse the unlimited language data. This software helps deliver lecturing comprehensively and is understood easily by students. Regarding to this application, it will make easier the student to learn, identify, and analyze the data in order to determine English word class within various texts. This study is concerned about how the process of teaching English word class using concordance software is conducted, and the students’ responses toward teaching English word class using concordance software. The corpus is taken from the British National Corpus (BNC). It is used to analyze word class categories (further discussed in Thomas, 1993). Concordance is available to be used both in English language teaching or linguistics field.